ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY - Azizah Azzah, St. Nur Al-Aina; Hasyim, Sitti Hajerah; Nuraisyiah, Nuraisyiah (Universitas Jabal Ghafur, 2024)
This research aims to analyze the factors that influence the disclosure of Corporate Social Responsibility (Empirical Study of Manufacturing Companies Listed on the IDX). The variables in this research consist of the independent variable (X), namely leverage, liquidity and company size and the dependent variable (Y), namely CSR disclosure. The population in this research is manufacturing companies in the cement subsector and paper sector listed on the Indonesia Stock Exchange. The sample in this study used a purposive sampling technique. Data collection was carried out using documentation techniques. This research uses descriptive analysis data, multiple linear regression and classical assumption tests. The results of this research show that the leverage and liquidity variables are not significant for CSR disclosure (Y), which means that H1 and H2 are rejected. Meanwhile, the company size variable (X) has a significant effect on CSR disclosure (Y), which means that H3 is accepted.